PERANCANGAN SISTEM PEMBUKUAN BERBASIS JAVA MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMMENT (STUDI KASUS: CANTIKA LIPRO) - Ahsana Nadya; Cantika Puan Maharani; Roibul Manun; Roeslan Djutalov (Journal of Research and Publication Innovation, 2023)
Bookkeeping management is important in an organization or company. In the era of increasingly advanced information technology, the use of computerized systems for bookkeeping has become an urgent need. The purpose of this research is to design a Java-based bookkeeping system using the Rapid Application Development (RAD) method to increase efficiency and accuracy in managing financial data. The RAD method is used to speed up the software development process by actively involving users in all stages of development. In this study, the RAD method was applied in designing a bookkeeping system to ensure that user needs are met and to provide flexibility in system development. In use, this system can help users to record, track, and print transaction data efficiently. This research contributes to the development of a Java-based bookkeeping system using the RAD method and can be a reference for further research in this field.